2017
DOI: 10.1186/s40781-017-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liposomal-curcumin on five opportunistic bacterial strains found in the equine hindgut - preliminary study

Abstract: BackgroundThe horse intestinal tract is sensitive and contains a highly complex microbial population. A shift in the microbial population can lead to various issues such as inflammation and colic. The use of nutraceuticals in the equine industry is on the rise and curcumin is thought to possess antimicrobial properties that may help to minimize the proliferation of opportunistic bacteria.MethodsFour cecally-cannulated horses were utilized to determine the optimal dose of liposomal-curcumin (LIPC) on reducing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As turmeric had not previously been experimentally studied in horses at the commencement of this study, a low dose of 20g daily (mean 37.9 ± 3.9mg/kg) was chosen as a conservative option for this initial study. Subsequent studies in horses [10] have evaluated similar doses (15, 20, 25 and 30g), while purified forms of curcumin have been trialled in horses at doses ranging from 1.06-15g [27,33]. Turmeric is considered safe with no toxic effects when administered orally in a number of species [34,35], and no negative effects were observed in this study.…”
Section: Journal Of Animal Science and Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…As turmeric had not previously been experimentally studied in horses at the commencement of this study, a low dose of 20g daily (mean 37.9 ± 3.9mg/kg) was chosen as a conservative option for this initial study. Subsequent studies in horses [10] have evaluated similar doses (15, 20, 25 and 30g), while purified forms of curcumin have been trialled in horses at doses ranging from 1.06-15g [27,33]. Turmeric is considered safe with no toxic effects when administered orally in a number of species [34,35], and no negative effects were observed in this study.…”
Section: Journal Of Animal Science and Researchmentioning
confidence: 94%
“…The two species have comparable biochemical composition and biological effects [8,9]. Many of these effects have been examined in cell-, animal-and human-based studies over the last decade or so and have demonstrated that both turmeric and its major bioactive component, curcumin, have antimicrobial, antioxidant, anti-cancer, anti-inflammatory and neuroprotective effects [10,11]. Several animal model and human studies have indicated the potential for turmeric/curcumin to prevent or treat gastric ulcers, with minimal side effects [12][13][14][15].…”
mentioning
confidence: 99%
“…Cecally cannulated horses were utilized to determine the optimal dose of curcumin LIP to reduce bacteria populations, including C. difficile , without adversely affecting cecal characteristics. The LIPs had no significant effect on C. difficile growth; on the contrary (at high doses), they increased opportunistic bacteria populations [ 131 ].…”
Section: Nanosystems As Antimicrobial Treatments Of Infectionsmentioning
confidence: 99%
“…Curcumin, which is produced by Curcuma longa L., is a natural phenol that promotes therapeutic properties such as anti-inflammatory, anticarcinogenic, and antioxidant activities [15][16][17]. Also, curcumin has been shown to be a bifunctional antioxidant that scavenges reactive oxygen species and triggers an antioxidant response to exert antioxidant activity both directly and indirectly [18,19].…”
Section: A C C E P T E D Introductionmentioning
confidence: 99%